Identification and distribution of immunocompetent cells in inflamed gingiva of human chronic periodontitis. - Okada, H (1983)
Advanced human periodontitis is considered to be a B-cell lesion, but the cellular infiltrate contains several cell types, the distribution of which has not been determined. This experiment was designed to characterize and identify the immunocompetent cells on histological sections and in eluates from diseased human gingiva. Immunoglobulin-bearing cells were detected on histological sections by direct immunofluorescence with F(ab')2 antisera monospecific for human immunoglobulin G (IgG), IgA, or IgM. Plasma cells predominated in the central portion of the lamina propria, with the proportions positive for IgG, IgA, and IgM accounting for 65.2 +/- 9.5, 11.2 +/- 1.1, and 1.3 +/- 1.1% of the total infiltrating cells, respectively. T lymphocytes, identified by indirect immunofluorescence with monoclonal antibody (Leu-1) against human T cells, accounted for 29.3 +/- 10.0% of the total infiltrated cells. Most of the T cells were located subjacent to the pocket epithelium, but there were a few in the central lamina propria. Similarly, Fc receptor-bearing cells detected by EA rosetting and macrophages and monocytes detected by nonspecific esterase staining with alpha-naphthylbutyrate esterase were also localized to the region immediately subjacent to the pocket epithelium. Infiltrated cells were harvested from minced gingival tissue after digestion with collagenase, hyaluronidase, and DNase. The eluates contained 35.3 +/- 6.0% T lymphocytes, 30.0 +/- 14.9% Fc receptor-bearing cells, and 12.9 +/- 4.4% monocytes and macrophages. Whereas T gamma cells comprised 13.3 +/- 1.4% of peripheral blood T cells, they accounted for only 6.0 +/- 2.0% of the eluate T cells. In contrast, T mu cells accounted for 44.7 +/- 4.9% of the T cells in the eluates and 51.6 +/- 4.4% in the peripheral blood. The decreased proportion of T gamma cells in the gingiva may indicate a form of abnormal immune regulation concerned with T suppression of B-cell proliferation.